AN ANALYSIS OF DIFFICULTIES IN WRITING ESSAY AT SECOND GRADE OF EDUCATION COLLEGE OF STKIP - Irsyad Nugraha (Institut Pendidikan Indonesia Garut, 2018)
Writing as one of the four skills in English has an important role for undergraduate students. This is because writing is productive skill which can build and rebuild the student’s motivation in mastering language. Writing is a basic skill for students, because it can improve students’ abilities in mastering language. In the process, writing skills has so many problems and solutions to enrich student’s capabilities.According to Harmer (2007), “writing is used as practice tool to help students practice and work with language they have been studying”. For example, ask a class to write five sentences using a given structure, or using five of the new words or phrases they have been learning. Writing activities like this are designed to give reinforcement to students. Another kind of writing for learning to occur is when we have students write sentences in preparation for some other activities. Brown (2001) claims that writing is a way of life, it means that in order to succeed in a course, students should express themselves with some oral skills and written skills about their ideas and abilities. When students can generate some ideas, thoughts and feelings in written, they have already succeeded to be creative students in processing some information.Population for this research is one purposed random sampling of second grade English Department students. The writer tries to get the sample only 20 students, which were taken from 90 students of second grade populations furthermore the writer tries to choose students with high cumulative mark and low cumulative mark to get the varieties problems of Essay Writing. The writer obtained the instrument of data by using some questionnaires and interview for students in order to analyze whether the problem of writing essay and teaching techniques of writing essays